STRATEGY CAMPAIGN "SENTUHAN KEHIDUPAN" OF JOHNSON & JOHNSON INDONESIA IN BUILDING CORPORATE IMAGE - Nursanti, Pradnya; Haryanti, Astrid (Social Economics and Ecology International Journal, 2018)
This research aims to identify the campaign strategy of Sentuhan Kehidupan from Johnson & Johnson Indonesia in building corporate image. The research method used is descriptive qualitative with data collection techniques in the form of semi-structured interviews, observation, documentation, and literature studies. The results of this research show that the campaign strategy is to perform problem analysis first, determine the objectives, messages, objectives, tactics, resources allocation time and evaluation methods.